1996
DOI: 10.1021/jo951504w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conjugation and Aromaticity on the Sulfoxide Bond1

Abstract: An ab initio computational study on a series of sulfoxides is reported. The SO bond dissociation energy (BDE) of sulfoxides in which the sulfur atom is included in a formally aromatic ring (e.g., thiophene sulfoxide) is found to be decreased by as much as 25 kcal/mol, compared to DMSO. A complementary effect is observed for sulfoxides in which the sulfur is included in a formally antiaromatic ring (e.g., thiirene sulfoxide), in which SO BDEs are increased by as much as 15 kcal/mol. Both effects are attenuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 44 publications
6
80
0
Order By: Relevance
“…In a previous computational work on sulfoxides in which S-O bond dissociation energies were determined by isodesmic exchange of the oxygen between a test sulfoxide and dimethyl sulfide, it was found that certain structural features led to significant differences in computed bond energies between Hartree-Fock and Møller-Plesset methods. 87 Moreover, Hartree-Fock methods are not generally reliable for predicting transition state energies. Therefore, it is not surprising to see a significant difference in the rotational barriers for PhSO • calculated by ROHF and RMP2 methods, though the magnitude of difference (2 kcal/mol Vs 13 kcal/mol) is large in this case.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous computational work on sulfoxides in which S-O bond dissociation energies were determined by isodesmic exchange of the oxygen between a test sulfoxide and dimethyl sulfide, it was found that certain structural features led to significant differences in computed bond energies between Hartree-Fock and Møller-Plesset methods. 87 Moreover, Hartree-Fock methods are not generally reliable for predicting transition state energies. Therefore, it is not surprising to see a significant difference in the rotational barriers for PhSO • calculated by ROHF and RMP2 methods, though the magnitude of difference (2 kcal/mol Vs 13 kcal/mol) is large in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other sulfur and selenium ylides, detailed thermochemical data allowing calculation of sulfoxide bond strengths are available for representative compounds. [23][24][25][26][27][28][29][30] Standard sulfoxide S-O BDEs are on the order of 87-90 kcal/ mol. Electronegative substituents raise the bond strength; for example, the BDE for F 2 SO is 114 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 On the other hand, conjugation of the sulfoxide to phenyl or vinyl substituents does not have a large effect. 29 However, the S-O bond strengths of thiophene derivatives are weakened because of the extra stabilization of the thiophene ring, compared to the nonaromatic sulfoxides. Previous calculations predict a BDE of about 65 kcal/mol for thiophene-Soxide.…”
Section: Introductionmentioning
confidence: 99%
“…We use generalized valence bond (GVB) theory to provide insights into the nature of the bonding in these molecules. A prior study of sulfur-oxygen compounds in our group showed that recoupled pair bonding involving the electrons in the p orbitals accounts for the strength of the SO bond in the ground X 3 R -state of diatomic SO, as well as for the large differences in geometry and SO bond strength of theX 2 A 00 states of HSO and SOH [17]. We found that a recoupled pair p bond is formed by the interaction of the electrons in the S3pp 2 lone pair and the O2pp 1 orbital in SO(X 3 R -).…”
Section: Introductionmentioning
confidence: 96%
“…Of interest here are molecules containing a single sulfinyl (SO) group with two additional ligands, which have the general formula XYSO. The SO bonds in these species are typically shorter and stronger than a standard single SO covalent bond [1], and their bond dissociation energies can vary significantly depending on the identity of the substituents (X, Y) [2]. Both the electronegativity and aromaticity of X and Y affect the SO bond dissociation energy.…”
Section: Introductionmentioning
confidence: 99%